Conceptual Evolution and Importance of Andragogy towards the Scope Optimization of University Academic Rural Development Programs and Projects - José Bernal Azofeifa-Bolaños (Universidad Nacional, Costa Rica, 2016)
This study was carried out with the objective of describing the evolution and importance of andragogical processes in the search of rural profiles committed to the university work in the development and implementation of programs and projects. Among its main contributions, the importance of knowing and teaching processes applied strictly for adults by university coordinators of programs and projects stands out. The relevance of applying this kind of knowledge will allow efficient use of institutional financial resources, particularly for the real commitment of the rural adult community towards the implementation of field activities and accomplishing, in a shorter term, the expected academic achievement. A successful project experience is described in which some andragogical strategies were applied through extension, and which produced a better participation and engagement from rural people with the projects developed by the University. Consequently, applicability of these concepts in the programs and projects of rural development promoted through universities must lay the foundation for regional rural development strategies with the ultimate goal of finding ways to improve the quality of life of people in particular scenarios.